The Idea of History in the Ancient Near East and the Old Testament. Translated by J. F. Ross - Gese, Hartmut (2012)
= Geschichtliches Denken im Alten Orient und im Alten Testament: Zeitschrift für Theologie und Kirche 55 (1958) 127-145.